Definitive high-dose, proton-based radiation for unresected mobile spine and sacral chordomas. (June 2022) - Banfield, Walter; Ioakeim-Ioannidou, Myrsini; Goldberg, Saveli; Ahmed, Soha; Schwab, Joseph H.; Cote, Gregory M.; Choy, Edwin; Shin, John H.; Hornicek, Francis J.; Liebsch, Norbert J.; Chen, Yen-Lin E.; MacDonald, Shannon M.; et al.
Highlights: High-dose radiation therapy should be considered for unresected chordoma patients. High-dose radiotherapy achieved by proton-based treatment has acceptable toxicity. Large tumor volume is associated with worse disease-free survival post-radiotherapy. Abstract: Background/Purpose: Treatment of spine and sacral chordoma generally involves surgical resection, usually in conjunction with radiation therapy. In certain locations, resection may result in significant neurological dysfunction, so definitive radiation has been used as an alternative to surgery. The purpose of this study is to report the results of high-dose, proton-based definitive radiotherapy for unresected spinal and sacral chordomas. Materials/Methods: Retrospective review of 67 patients with newly diagnosed, unresected spinal chordomas treated with high-dose definitive, proton-based radiotherapy at our center from 1975 to 2019. Results: Reasons for radiotherapy alone included medical inoperability and/or concern for neurological dysfunction based on spine level or patient choice. Tumor locations included cervical ( n = 10), thoracic ( n = 1), lumbar ( n = 4) spine, and sacrum ( n = 52). Median maximal tumor diameter was 7.4 cm (range 1.8–25 cm). Median total dose was 77.4 Gy (RBE) (range 73.8–85.9 Gy RBE). Analysis with median follow-up of 56.2 months (range, 4–171.7 months) showed overall survival of 83.5 % (95%CI: 69.4–91.5%) and 65.9% (95%CI: 47.3–79.3%), disease-free survival of 64% (95%CI: 49.3–75.4) and 44.1% (95%CI: 27.8–59.2%), local control of 81.8% (95%CI: 67.6–90.2%) and 63.6% (95%CI: 44.7–77.5%), and distant control of 77.4% (95%CI: 63.6–86.5%) and 72.5% (95%CI: 55.7–83.8%) at 5 and 8 years respectively. The most common late side effect was insufficiency fracture. Conclusion: These results continue to support the use of high-dose definitive radiotherapy for patients with medically inoperable or otherwise unresected mobile spine or sacrococcygeal chordomas. There is a trend towards better disease-free survival with doses > 78 Gy (RBE).